Ground-based investigation of a directional, flexible, and wireless concentrated solar energy transmission system. (15th September 2022) - Wang, Ji-Xiang; Zhong, Mingliang; Wu, Zhe; Guo, Mengyue; Liang, Xin; Qi, Bo
Highlights: A flexible concentrated solar energy wireless transmission system was developed. It uses the space sunlight to overcome intermittency of the solar energy application. Optimal energy transmission modelling and experimental validation was conducted. Maximum transmitter energy transmission efficiency of 52.0% was obtained experimentally. Power/weight ratio of the system could be increased by 17.0% by comparing parallels. Abstract: Solar energy in space is more intensive and continuous compared to that on the Earth, and thus, is encouraged by governments across the world to be utilized for human beings. The continuity of the space sunlight has a great potential to overcome the bottleneck of the variability and intermittency in time and space for ground-based solar energy applications. Space solar power station (SSPS) is known as intermedia that can harvest the space solar energy and transmit it wirelessly to the end-user. However, the current wireless energy transmission via microwave or laser suffers from low energy transmission efficiency because of excessive energy conversion processes. Wireless energy transmission via sunlight without any intermediate energy conversion process was proposed previously theoretically for high energy transmission efficiency, but it also lacks practicability due to heavyweight and inflexibility. Therefore, although promising, practical sunlight-based wireless energy transmission proposals have not ever been presented. Here, through component and structure optimizations in theoretical and experimental approaches, a novel and more practical concentrated solar energy wireless transmission system that transmits the harvested sunlight via lightweight optical fibers is proposed in this paper. It uses a Fresnel lens to collect concentrated solar energy and then, the utilized optical fiber can steer the collected energy to the collimator flexibly. At last, a parallel sunlight beam can be emitted from the collimator to the target end-user. Results show that the transmitter efficiency versus optical fiber length exhibited a linear relationship from both theoretical and experimental approaches. the cloud effect harmed the energy transmission. A maximum transmitter energy transmission efficiency of 52.0% could be attained experimentally. Compared with the performance in the no-cloud condition, the gained voltage could be declined by 37% ∼ 48%. The bending of the optical fiber seemed to not affect much on the energy transmission performance, which guarantees a flexible energy transmission. Besides, the power/weight ratio was increased by 17.0% compared to its counterpart. The innovation of this paper is to reduce the gap between theoretical and practical feasibilities for the proposed system. This paper experimentally demonstrates the feasibility of a wireless concentrated solar energy transmission technology, which promotes the application of SSPS and related aerospace applications.